REVISITING THE CONCEPT OF GURU IN VARIOUS CULTURAL PERSPECTIVES - Andrias Tri Susanto (Widya Mandala Surabaya Catholic University, 2018)
Teacher education institutions worldwide have mostly attempted to shape their candidate teachers with positive traits of an effective teacher. However, this notion of equipping the future teachers with features of an ideal figure of a teacher seems to be obscure without any comprehensible identifications of what the features are. This study was then written to report an analytical review on the conception of a great teacher under the noble idea of guru as understood in Javanese and Indian culture. By understanding the various cultural perspectives of the term ‘an ideal teacher’ and identifying the characteristics of guru¸ this article can later be used as a foundation of defining what type of a teacher that a teacher education institution has been working on. This was conducted through literature review and analytical qualitative study of some candidate teachers taking Micro Teaching course in the Faculty of Teacher Training in Widya Mandala Catholic University Surabaya. This study attempted to identify connections between the proposed theories discussed and personal perspectives of the candidate teachers conveyed through their reflective writing products.